Islamic Boarding Schools' Foreign Language Goals: A Dual-Language Sinking Model (Program Studi Pendidikan Agama Islam, 2023)
This study was motivated by the failure of language learning from traditional methods. This method does not provide a chance for students to practice the language that makes the alinated from the target language. On this basis, Dual-Language Sinking model was developed for language learning which will bridge learning with the daily lives of students to achieve the expected language competencies.This literature review will try to explore what language competencies are needed by students to be said as language competent users and what are the ideal patterns of language learning to develop their language competencies. Finally, the Dual-Language Sinking model will be explained as a offered model to develope language competencies and how to implement the model. The results of this study indicate that competent language users are those who are able to function their language skills and knowledge in their daily activities. To develop students who are competent in language, the learning conditions must be designed as naturally as possible as students' first language environment. This can be achieved by implementing a dual-language sinking as bilingual program. This model uses the target language as the language of instruction in learning and students' daily lives, so that students will develop their language competence through their daily habits.